2021
DOI: 10.1017/s1047951121001943
|View full text |Cite
|
Sign up to set email alerts
|

The role of the neutrophil–lymphocyte ratio for pre-operative risk stratification of acute kidney injury after tetralogy of Fallot repair

Abstract: Introduction: Acute kidney injury is a risk factor for chronic kidney disease and mortality after congenital heart surgery under cardiopulmonary bypass. The neutrophil–lymphocyte ratio is an inexpensive and easy to measure biomarker for predicting outcomes in children with congenital heart disease undergoing surgical correction. Objective: To identify children at high risk of acute kidney injury after tetralogy of Fallot repair using the neutrophil–lymphocyte ratio. Methods:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 24 publications
1
13
2
Order By: Relevance
“…In the current study, preoperative NLR was not an independent risk factor for predicting postoperative adverse outcomes, which was different from the conclusions of previous studies [ 8 , 27 , 29 ]. Although preoperative NLR was associated with mechanical ventilation time and length of ICU stay like other studies, the small coefficient indicated a weak correlation.…”
Section: Commentcontrasting
confidence: 99%
“…In the current study, preoperative NLR was not an independent risk factor for predicting postoperative adverse outcomes, which was different from the conclusions of previous studies [ 8 , 27 , 29 ]. Although preoperative NLR was associated with mechanical ventilation time and length of ICU stay like other studies, the small coefficient indicated a weak correlation.…”
Section: Commentcontrasting
confidence: 99%
“…Of 404 cyanosis patients (44.9%) in 6 studies, 24,26,27,29,31,33 210 patients underwent CHD repair and 194 patients underwent surgical palliation (Table 1). A total of 193 patients (50.2%) were noted to have TOF.…”
Section: Prognostic Value Of Nlr In Congenital Heart Surgerymentioning
confidence: 99%
“…29 Further evaluation of this group of patients demonstrated that a higher NLR was associated with grade III AKI ( P = .040). 33…”
Section: Prognostic Value Of Nlr In Congenital Heart Surgerymentioning
confidence: 99%
“…29 As one of the most common components of the systemic inflammatory response, lymphocytes are well-known inflammatory markers involved in AKI. Increasing studies have taken the lymphocyte-based serum inflammatory biomarkers into consideration for the development of AKI and prognosis of patients in different populations, such as neutrophil-tolymphocyte ratio, 8,30,31 platelet-to-lymphocyte ratio, 32,33 prognostic nutritional index 34,35 and so on. However, limited data have focused on the combination of inflammatory factors and glucose metabolic factor.…”
Section: Dovepressmentioning
confidence: 99%
“…[1][2][3][4] Among them, cardiac surgery-associated AKI (CSA-AKI), as the second most common cause of AKI for ICU patients, is independently associated with increased morbidity and mortality, prolonged length of hospital stays and increased healthcare costs. [5][6][7][8] It is currently acknowledged that timely identifying patients at high risk of AKI and then providing appropriate interventions at an early stage could improve the prognosis of AKI patients. [9][10][11] Hence, a novel biomarker with high prediction accuracy and easily accessible is essential for clinicians in immediate and appropriate decision-making regarding treatment options.…”
Section: Introductionmentioning
confidence: 99%